Public Organization Participation in the Prevention of Sexual Crimes against Minors and Adolescents: International Practices - Saltanat Azhibekova; Bibigul Kulmukhanbetova (Wolters Kluwer Medknow Publications, 2024)
Background: The study of how to prevent crimes against kids' and adolescents' sexual freedom and inviolability is an ongoing topic of interest for scientific-legal doctrine. In Kazakhstan, the trend of the dynamics of committing such crimes is relatively high, as in other countries, which indicates the need to change approaches and means to prevent such sexual offenses. Aim and Objective: The goal of this study is to analyze statistical data on the number of crimes against minors and adolescents' sexual integrity in Kazakhstan, as well as the effectiveness of domestic and international best practices in combating this issue, as well as the level of public sector involvement in this process. Materials and Methods: The issue under study is quite broad in its content; therefore, several scientific and methodological tools were used for its in-depth study. The functional and dialectical approaches are specifically mentioned, along with the methods of analysis and synthesis, comparison, formal-legal procedure, and generalization. Results: Both theoretical and practical facets of the issue under investigation were examined as a result of the research that was done. Accordingly, at the beginning of the study, all the necessary theoretical foundations for a qualitative understanding of the research object are covered. Conclusions: The practical part of the study determines the effectiveness of the available methods for preventing sexual crimes against minors and adolescents, considers the regulations governing this type of criminal offense, and analyses the approaches and tools used by foreign countries in this area.